Human Resource Management Practices In Procurement Employees at PT. Unhas Hotel And Convention - Adrianah; Rukama Sari (IECON: International Economics and Business Conference, 2024)
This study aims to determine the description or picture of Human Resource Management Practices in Employee Procurement at PT. Unhas Hotel and Convention. Data collection in this study uses the Observation and Interview methods. The type of research used in this study is descriptive with a qualitative approach in the form of non-statistics. Based on the results of the study on "Human Resource Management Practices in Employee Procurement at PT. UnhasHotel and Conventionit can be concluded that the practice of human resource management in employee procurement at PT. UnhasHotel and Conventionimplemented in accordance with the company's Standard Operating Procedures. Although it helps departments to get qualified employees, this process often takes a long time due to candidate incompatibility. Recruitment is carried out openly or closed through various media, and through strict selection stages according to the qualifications of the workforce needed. However, most employees are recruited from within the company, causing certain vacancies. Internal recruitment also has the potential for a lack of fresh ideas from newcomers and a lack of encouragement for further work performance.